Giant ameloblastoma of the mandible - Pranjal Rai, MD; Fabien Necker, MD; Animesh Awadhiya, MBBS; Joe Joseph, MD; Dhairya A. Lakhani, MD (Radiology Case Reports)
Ameloblastoma is a benign odontogenic tumor characterized by slow, asymptomatic growth and local aggressiveness. We report a case of a 24-year-old female with a gradually enlarging, painless swelling on the left side of her mandible over 3 years. Imaging revealed a 12 × 8 cm multilocular radiolucent lesion with cortical thinning and perforation, extending from the premolar to the angle of the mandibular ramus. Differential diagnoses included odontogenic keratocyst, dentigerous cyst, and other radiolucent mandibular lesions, and histopathological analysis confirmed a solid/multicystic ameloblastoma. The patient underwent segmental mandibulectomy with immediate reconstruction using a free fibular flap. Postoperative recovery was uneventful, and no recurrence was observed during one year of follow-up. This case highlights the importance of early recognition of asymptomatic jaw swellings, integration of imaging and histology for diagnosis, and radical surgical management for extensive lesions. Prompt intervention can reduce morbidity and optimize long-term outcomes in young patients.